If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2x + -5) + -4(x + -20) = x + -5 Reorder the terms: 7(-5 + 2x) + -4(x + -20) = x + -5 (-5 * 7 + 2x * 7) + -4(x + -20) = x + -5 (-35 + 14x) + -4(x + -20) = x + -5 Reorder the terms: -35 + 14x + -4(-20 + x) = x + -5 -35 + 14x + (-20 * -4 + x * -4) = x + -5 -35 + 14x + (80 + -4x) = x + -5 Reorder the terms: -35 + 80 + 14x + -4x = x + -5 Combine like terms: -35 + 80 = 45 45 + 14x + -4x = x + -5 Combine like terms: 14x + -4x = 10x 45 + 10x = x + -5 Reorder the terms: 45 + 10x = -5 + x Solving 45 + 10x = -5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 45 + 10x + -1x = -5 + x + -1x Combine like terms: 10x + -1x = 9x 45 + 9x = -5 + x + -1x Combine like terms: x + -1x = 0 45 + 9x = -5 + 0 45 + 9x = -5 Add '-45' to each side of the equation. 45 + -45 + 9x = -5 + -45 Combine like terms: 45 + -45 = 0 0 + 9x = -5 + -45 9x = -5 + -45 Combine like terms: -5 + -45 = -50 9x = -50 Divide each side by '9'. x = -5.555555556 Simplifying x = -5.555555556
| 5+30x=15+11 | | Y=20+.2x | | 3x=-9y+33 | | y=mx+c(c) | | 7s+6=8s+15 | | 7p-5p=20 | | 4j=7j+6 | | Y=4x^2-3x^3 | | 6-(3y-8)=5-4y | | -z=-4z+6 | | 6.4(x-4)=19.5 | | -w=-5w+16 | | 3z/4=2z/3-5 | | -10x=75 | | -8-b/5=-10 | | (2*x/((14/10)*x)=0 | | 9.2(x+6.4)=124.48 | | -2-k/2=-8 | | a/6+1=11 | | 8d-7=32 | | y/7-1=8 | | 10-8e=18 | | 1.5(c+7)=-37.35 | | (8x^2y)/(12x^4y^4) | | -7-5q=-47 | | 7-5q=-47 | | -86=4c | | 5(n-2)-(6-4n)=8n | | 9x+10-6x=9+2x-6 | | -6(X+9)=20 | | 5-p=9 | | 10x+(8x-16)+(12x-8)+(7x+2)+(9x+4)(6x+10)= |